2006
DOI: 10.1207/s15327604jaws0901_2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Induced Molting on the Well-Being of Egg-Laying Hens

Abstract: Induced molting in egg-laying hens is an important method for maximizing hen egg production and quality as well as hen health in commercial settings; however, there is growing societal concern over its effects on hen well-being. Using individual hens as their own controls, this research examined the behavior of hens subjected to different treatments of induced molting under premolt, molt, and postmolt conditions. Cage pecking increased in fast-induced subjects and aggression increased in fast-induced and nonfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…The increased preening may be due to sensitivity from the loss of feathers (Webster, 2000) or displacement behavior (an unrelated behavioral response to anxiety) as a result of frustration (Duncan and Wood-Gush, 1972). The increase in nonnutritive pecking agrees with research by McCowan et al (2006), who reported an increase in cage pecking for hens assigned to an FW and a non-FW molt during the molt period compared with the premolt period. This increase may be due to hunger or a redirection of foraging behaviors (Webster, 2003).…”
Section: Pre-vs Postmoltsupporting
confidence: 82%
See 4 more Smart Citations
“…The increased preening may be due to sensitivity from the loss of feathers (Webster, 2000) or displacement behavior (an unrelated behavioral response to anxiety) as a result of frustration (Duncan and Wood-Gush, 1972). The increase in nonnutritive pecking agrees with research by McCowan et al (2006), who reported an increase in cage pecking for hens assigned to an FW and a non-FW molt during the molt period compared with the premolt period. This increase may be due to hunger or a redirection of foraging behaviors (Webster, 2003).…”
Section: Pre-vs Postmoltsupporting
confidence: 82%
“…Anderson et al (2004) reported that feather pecking increased during a 2-wk FW for hens kept in a cage system (6 hens/cage at 361 or 482 cm 2 /hen), but the frequency of aggressive and submissive acts was lower during the same time period. Webster (2000) and Biggs et al (2004;housed 3 hens/cage at 460 cm 2 /hen) reported no differences in aggressive pecking behaviors when comparing WM and FW molt treatments, but McCowan et al (2006) noted that cage pecking increased in hens (housed 3 hens/cage at 417 cm 2 /hen) assigned to an FW molt, and aggression increased in hens assigned to an FW and a non-FW molt during the molt period. Webster (2000), Anderson et al (2004), and Biggs et al (2004) reported in agreement across studies that FW birds did not show an increase in aggression, nonnutritive pecking, or sitting when compared with birds that still had access to a low-energy feed during molt.…”
Section: Low-energy Molt Diets Pre-and Postmoltmentioning
confidence: 96%
See 3 more Smart Citations